2015
DOI: 10.1007/s12253-015-9990-z
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-1 as a Biomarker of Cervical Cytology and Histology

Abstract: Several immunochemistry tests are used for triaging human papilloma virus (HPV) and cytology positive cases in cervical cancer screening and as an adjunct test to diagnose cervical cancer. Claudin-1 (CLDN1) protein is a major component of the tight junction, shown to have altered expression in cervical cancer. In this study, value of CLDN1 was analysed as a screening and triage immunochemistry test compared to cytology and HPV testing. A population of 352 women attending colposcopic referral visits resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
2
13
1
Order By: Relevance
“…Dysregulation of claudin-1 has previously been demonstrated to be involved in tumorigenesis and progression in various malignant entities, including cervical cancer (2,5). The pivotal role of claudin-1 in tumorigenesis has been hypothesized in the context of the pre-cancerous (8). However, the findings of the current study did not determine any significant association between the claudin-1 expression levels in the cervical cancer patient cohort and the tumor size, FIGO stage or grade.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Dysregulation of claudin-1 has previously been demonstrated to be involved in tumorigenesis and progression in various malignant entities, including cervical cancer (2,5). The pivotal role of claudin-1 in tumorigenesis has been hypothesized in the context of the pre-cancerous (8). However, the findings of the current study did not determine any significant association between the claudin-1 expression levels in the cervical cancer patient cohort and the tumor size, FIGO stage or grade.…”
Section: Discussioncontrasting
confidence: 90%
“…INK4a and claudin-1 expression in pre-invasive cervical lesions (8). Consequently claudin-1 could serve as a marker for pre-invasive lesions and early invasive cervical carcinoma.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Claudin‐4 was reported positive in 97% of effusion samples from patients with ovarian, lung and endometrial carcinomas, and in one patient with pancreatic carcinoma, with these carcinoma cells showing strong and diffuse immunopositivity . Claudin‐1 expression was observed as linear membrane positivity on cervical smear samples . In our study, Claudin‐18 was distributed along the entire cell membrane of most adenocarcinoma cells but was almost completely absent from non‐neoplastic epithelial cells.…”
Section: Discussionsupporting
confidence: 48%
“…Claudin‐18 is detected in gastrointestinal and lung tissues and was shown to be overexpressed immunohistochemically in pancreatic and biliary duct adenocarcinomas. Although few studies reported that Claudin‐4 or Claudin‐1 expression was present in the effusion or cervical samples, to our knowledge no study has evaluated Claudin‐18 expression on alcohol‐fixed cytology smears.…”
Section: Introductionmentioning
confidence: 97%